AKUNTANSI SUMBERDAYA MANUSIA: PERLAKUAN DAN PENGUKURAN - Sudarno, Sudarno (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2010)
The objective of this study is to examine the accounting treatment for human resource, whether human resource is recognized as an asset or as a periodical expense. Conventional accounting believe that investment on human resources is recognized as cost as its occured. However, investment on human resources meets criteria as an expense and also as an invesment which need to be capitalized. From various measurement method on human resource, the writer believe that human resources should be recognize as an asset and the best measurement method is historical cost since this method is more reliable and objective method. Keywords: human resources accounting, measurement of HRA